An overview of methods to detect biodegradation limiting conditions - Matos Cruz, Jaqueline [UNESP]; Montagnolli, Renato Nallin [UNESP]; Claro, Elis Marina Turini [UNESP]; Quitério, Gabriela Mercuri [UNESP]; Moraes Júnior, José Rubens [UNESP]; Matos Lopes, Paulo Renato [UNESP]; Bidoia, Ederio Dino [UNESP] (Springer Nature, 2018)
The chapter discusses some limitations to perform the successful results obtained with two methodologies widely used in laboratory scale to environmental conditions. Certainly, the microorganisms are the most important tools for the biodegradation process. For this reason, the biodegradability of any compound requires an active microbial consortium or an adequate succession of microorganisms. Also, the conditions to guarantee the microbial growth must be provided, such as micro and macronutrients, final electrons acceptor, optimal temperature, and range of suitable pH. We considered the temperature and pH as powerful factors to the biodegradation process, because the temperature defines the growth rate of the microorganisms and the pH plays a role in selecting the microorganisms per the different range of pH. In this chapter, we discussed how the natural biodegradation process, subject to dynamic environmental conditions such as temperature, pH range, and microbial succession, can possibly differ of experiments in controlled laboratory conditions.
Keywords: Bioremediation; Colorimetry; Respirometry; Toxicity